Quality Attributes of Suya from Indigenous Goat Breeds (Bucks) in Nigeria: Introduction - Ayanniyi, N. N.; Olusola, O. O.; Adeyemi, S. A.; Gbanguba, A. U.; Umar, A.; Eze, J. N.; Orimogunje, A. D. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2022)
A study was conducted to evaluate the percentage yield (%), proximate composition and organoleptic evaluation of the freshly prepared Suya product from indigenous goat (buck) breeds in Nigeria .Thigh muscle with average weights of 3.1±0.2 kg was excised from the carcasses of 9 fully matured bucks managed intensively for 90 days. The Chevon were dissected into smaller pieces of 10 cm long. The meat samples were thereafter trimmed of visible fats. They were also finely trimmed to very thin sheets of meat about 0.22 - 0.32 mm in thickness and with a length of about 4.5 cm - 9.3 cm. A total of 99 Suya sticks was prepared with 11 from each buck weighing approximately 88.50 g per stick. Suya ingredients used for the experiment were sourced from Bodija Market, Ibadan. The results showed that weight losses were considerable in all the treatments but the yield was not significantly different (P>0.05) among the breeds. There was also no significant difference in moisture contents among the treatment groups while the protein, ether extract and crude fibre differed significantly across the treatments. Texture of Suya from Sahel bucks with 6.81±0.3 was significantly higher than 5.4±0.3 and 5.5±0.4 for WAD and Red Sokoto bucks respectively. The overall acceptability of Suya from Sahel bucks with 6.24 and Red Sokoto bucks with (6.9±0.1) were similar and most accepted than 5.10 of that from West African dwarf bucks.